(untitled) (Malay Literature, 2019)
Interlok is a literary work with a specific theme that resulted from a contest and it proposes the subject of national integration at its core to fulfil the aspirations and the development of the then newly independent Malaysia. The historical framewor k is used as an instrument for discourse purposes in addressing socio-cultural and humanitarian issues related to the solidarity and development of the Malaysian nation. Therefore, this novel may be categorised as a socio-historical novel and not purely a historical novel. Interlok provides the opportunity to the reader to explore the author’s profound meaning in introducing the subject of solidarity as the foundation of the development of the Malaysian nation. The difference in values among the races has to be narrowed whereas the quality or the advantage possessed by each of the respective races has to be assembled to obtain maximum benefit. Keywords: Interlok, historicising fiction, fictionalising history, solidarity, socio-cultural, socio-historical